Supplier Evaluation with Hesitant Fuzzy Analytic Hierarchy Process in Bearing Sector and Consistency Analysis - (:unkn) unknown (AMER SOC TESTING MATERIALS, 2020)
The bearing sector has a demand for high precision and expensive machine tools. To ensure product quality and reduction of operating costs, the manufacturers in this sector should develop an appropriate supplier evaluation mechanism for the bearings. Therefore, this study presents a Hesitant Fuzzy Analytic Hierarchy Process (HF-AHP) technique for the evaluation of suppliers. HF-AHP, which is an extension of the well-known Fuzzy AHP (F-AHP), allows more space to decision makers while they are performing pairwise comparisons in hesitant situations. This article also introduces a consistency analysis technique for the preferences. This technique firstly sorts out the hesitancy and then deals with fuzzy comparisons. In addition, to demonstrate the applicability of the proposed approach, a case study is presented as a numerical example in the bearing industry. The results of this application are compared with the results of the same case that was previously handled with the traditional F-AHP method in the literature. Finally, sensitivity analysis, which is performed to check the robustness of the decision, investigates the effects of changes in criteria weights.
Keywords: bearing sector; supplier evaluation; hesitant fuzzy analytic hierarchy process; consistency analysis; LINGUISTIC TERM SETS; DECISION-MAKING; AHP; SELECTION; DISTANCE